The impact of low dietary inflammatory index diet on clinical parameters in patients with chronic kidney disease: a retrospective comparative study - Weijuan Pan; Jian Feng (BMC Nephrology)
Abstract Background Chronic kidney disease (CKD) poses a significant global health challenge. Inflammation plays a central role in the pathogenesis and progression of CKD, which has been proved to be affected by dietary patterns. To understand how dietary inflammatory index (DII) impacts the disease course and clinical parameters, we aim to explore the relationship between DII and multiple clinical parameters in a specific cohort of CKD patients, and to provide insights into the potential of dietary for managing CKD. Methods This retrospective comparative study included 145 CKD patients, categorized into a low DII group (n = 77) and a high DII group (n = 68) based on their DII values. Clinical data, including demographic characteristics, laboratory parameters, dietary intake, inflammatory markers, renal function, and adverse events, were collected and compared between the two groups. Results The demographic characteristics were comparable between the groups. The low DII group had significantly lower serum creatinine, phosphorus, and potassium levels (P < 0.05) and higher hemoglobin levels compared to the high DII group. Protein intake was significantly higher in the high DII group (P < 0.001), while fiber intake was significantly higher in the low DII group (P = 0.022). Inflammatory markers, including CRP, TNF-α, fibrinogen, procalcitonin, and WBC, were significantly lower in the low DII group (P < 0.05). The low DII group also showed better renal function, as indicated by higher GFR and lower urinary albumin excretion (P < 0.05). Correlation analysis revealed significant relationships between protein intake and inflammation markers (CRP, TNF-α, fibrinogen) and a negative correlation with GFR. Regression analysis confirmed that DII was independently associated with CRP, GFR, and urinary albumin excretion, while protein intake remained significantly correlated with these outcomes. Conclusion A low DII diet may be associated with improved clinical parameters, inflammatory markers, and renal function in CKD patients. Tailored nutritional strategies focusing on modulating inflammatory status through low DII diets may offer promising avenues for improving renal function, mitigating inflammation, and enhancing overall well-being in individuals with CKD. Clinical trial number Not applicable.